Exome sequencing identifies a recurrent variant in SERPINA3 associating with hereditary susceptibility to breast cancer. (January 2021) - Koivuluoma, Susanna; Tervasmäki, Anna; Kauppila, Saila; Winqvist, Robert; Kumpula, Timo; Kuismin, Outi; Moilanen, Jukka; Pylkäs, Katri
Abstract: Background: Breast cancer is strongly influenced by hereditary risk factors. Yet, the known susceptibility genes and genomic loci explain only about half of the familial component of the disease. To identify novel breast cancer predisposing gene defects, here we have performed massive parallel sequencing for Northern Finnish breast cancer cases. Methods: Ninety-eight breast cancer cases with indication of hereditary disease susceptibility were exome sequenced. Data filtering strategy focused on predictably deleterious rare variants that were still enriched in the sequenced cohort. Findings were confirmed with additional, geographically matched breast cancer cohorts. Results: A recurrent heterozygous splice acceptor variant, c.918-1G>C, in SERPINA3, was identified, and it was significantly enriched both in the hereditary (6/201, 3.0%, p = 0.006, OR 5.1, 95% CI 1.7–14.8) and unselected breast cancer cohort (26/1569, 1.7%, p = 0.009, OR 2.8, 95% CI 1.3–6.2). SERPINA3 c.918-1G>C carriers were also significantly more likely to have a rare tumor subtype, medullary breast cancer, than the non-carriers (4/26, 15.4%, p = 0.000014, OR 42.9, 95% CI 11.7–157.1). Conclusion: These findings demonstrate that c.918-1G>C germline variant in SERPINA3 gene, encoding a member of the serine protease inhibitor class, is a novel breast cancer predisposing allele. Highlights: Breast cancer has a strong inherited component that causes familial clustering. Using exome sequencing we establish SERPINA3 as a novel predisposing gene. This provides further tools for the clinical breast cancer risk assessment. SERPINA3 encodes as a plasma protease inhibitor frequently aberrated in cancer. Function of SERPINA3 proposes new mechanisms for breast cancer pathogenesis.